The Effect of Competency and Working Environment on Employee Performance through Motivation as Intervening Variable: The Case of Bank Sumsel Babel Syariah Palembang Branch - Elianora, Elianora; Idris, Muhammad; Trihandayani, Zaleha (International Journal of Business, Management and Economics, 2025)
This study aims to determine the effect of competency and work environment on employee performance, with motivation serving as an intervening variable. The subjects of this study were employees of Bank Sumsel Babel Palembang Syariah Branch. The sampling technique employed was probability sampling, utilizing a cluster random sampling method. The research method employed was associative research, utilizing primary data collected through questionnaire responses. The analysis technique used was structural equation modeling (SEM). The result of this study : (1) There is a significant influence of competence on employee performance at Bank Sumsel Babel Palembang Syariah Branch, (2) There is a significant influence of work environment on employee performance at Bank Sumsel Babel Palembang Syariah Branch, (3) There is a significant influence of competence on motivation at Bank Sumsel Babel Palembang Syariah Branch, (4) There is a significant influence of work environment on motivation at Bank Sumsel Babel Palembang Syariah Branch, (5) There is a significant influence of motivation on employee performance at Bank Sumsel Babel Palembang Syariah Branch.